Biosorption property of modified and unmodified of hybrid biosorbent of mangrove bark and lignocellulosic (Oil Palm Fiber) toward heavy metals / Bebe Norlita Mohamed … [et al.] - Mohamed, Bebe Norlita; Mohamadin, Mohammad Isa; Micheal, Nicodemus Ujih (2017)
Chemical water pollution in water bodies has trigger and create awareness among researchers on health effect of heavy metals toward living organisms and how to control chemical pollution from worsening. This pollution mainly comes from the industrial wastewaters that are discharged without being treated. Besides, due to the expensive material of conventional method, it is not suitable to be used to treat heavy metals in long term, however by using biomass as an adsorbent; it is cheaper and eco-environmental due to abundant resources of agricultural wastes. In this research, two types of biomass were used as biosorbenst, which were hybridized together to form hybrid biosorbent (HB): oil palm mesocarp fiber (OPMF) (Elaesis guineensis sp.) and mangrove bark (MB) (Rhizophora apiculate sp.). The similarity between these biomasses is they can absorb multiple heavy metal ions (Cr, Cu, Ni, and Pb) at one time. Thus, by hybridizing these biosorbents, the adsorption capacity can be maximized compared with single biosorbent. The adsorption capacity was also investigated based on four parameters namely contact time, initial concentration, ratio/dosage and pH values. It was found that the adsorption capacity of HB was higher than OPMF and MB; and the results revealed that metals adsorption was in the order: Pb2+>Cu2+>Ni2+>Cr2+.